60 GHz compact broadband antenna arrays with wide‐angle beam steering. Issue 8 (13th June 2019) - Aziz, Imran; Dahlbäck, Robin; Öjefors, Erik; Sjögren, Kristoffer; Rydberg, Anders; Dancila, Dragos
Abstract : Highly integrated multilayered printed circuit board‐based patch antenna arrays are proposed in this study for 60 GHz wireless communications. Electromagnetic coupling between two stacked patches is used to achieve the broadband performance. Different structures of single element antennas, two‐element antenna arrays and four‐element antenna arrays are presented. The two compact four‐element antenna arrays show < −10 dB impedance bandwidth of 13 and 14.6% with 12 dBi peak gain. The arrays have the 3 dB gain bandwidth of 9 and 13%. A single column, four‐element sub‐array is used to design 4 × 16 antenna array. This array delivers 20.8 dBi peak gain with 13% impedance and gain bandwidth. Furthermore, a two‐element series fed array is used to realise a 2 × 16 phased antenna array. This array is fed through a 16 × channel radio frequency IC to achieve the beam steering in ± 50 ° range.